IMPLIKASI UNDANG-UNDANG NOMOR 14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK PADA INFORMASI TEKNOLOGI PENGELOLAAN AIR BERSIH DAN LIMBAH CAIR - Komarudin, Komarudin; Wahjono, Heru Dwi (Jurnal Air Indonesia, 2008)
Since the Internet was introduced virtual network, the globalization of information gradually changes. One positive result of the globalization of this information is the geographical boundaries are not visible in the face of the earth. Information wide open to anyone who would like to access and contribute in it. To protect the rights and obligations of both the information providers and the users from the cyber crime, the government has prepared several law and legislation. On this paper, the regulation of public information opennes (Law Number 14/2008) will be discussed, which protect the rights of people to access information held by public agencies and institutions. Example given is associated with the provision of information for environmental problems, particularly water management technology and liquid waste that has been managed by the Center for Environmental Technology, Agency for the Assessment and Application of Technology.Ã‚Â Keywords : Keterbukaan Informasi Publik, Pelayanan Informasi Teknologi, Hak Akses, Jaringan Global Internet, Hubungan Masyarakat, Cyber Crime, dan Good Gevernance